2009
DOI: 10.1111/j.1399-0039.2009.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of MICA diversity in the Chinese Han population by polymerase chain reaction sequence‐based typing for exons 2–6

Abstract: Major histocompatibility complex class I chain-related gene A (MICA) is located 46 kb centromeric to HLA-B locus and encodes a stress-inducible protein. MICA allelic variation is thought to be associated with disease susceptibility and immune response to transplants. In this study, polymerase chain reaction sequence-based typing (PCR-SBT) method for MICA alleles has been established. Genomic DNAs from 100 healthy Chinese Han individuals were typed for MICA alleles by this method. The microsatellite polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
2
15
1
Order By: Relevance
“…Similar MICA frequencies were observed among different Chinese ethnic groups; with the exception of MICA*019, which was higher in frequency (14.93%) in our cohort compared with other Chinese populations (3.85 [22] and 9.5% [23]). In the northern Chinese population, Tian and co-workers reported a lower frequency of MICA*12:01, MICA*019 and a higher frequency of MICA*004 [24].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar MICA frequencies were observed among different Chinese ethnic groups; with the exception of MICA*019, which was higher in frequency (14.93%) in our cohort compared with other Chinese populations (3.85 [22] and 9.5% [23]). In the northern Chinese population, Tian and co-workers reported a lower frequency of MICA*12:01, MICA*019 and a higher frequency of MICA*004 [24].…”
Section: Discussionsupporting
confidence: 88%
“…In the northern Chinese population, Tian and co-workers reported a lower frequency of MICA*12:01, MICA*019 and a higher frequency of MICA*004 [24]. Deviations of MICA frequencies (MICA*045, -*027, and -*008:01) between our cohort and the population of Zhejiang Province in middle China [23] were observed.…”
Section: Discussioncontrasting
confidence: 61%
“…To characterize the differences in MICA gene polymorphisms between the distinct ethnic groups, which may modify the susceptibility of different groups to schistosomiasis or affect associated pathologies, we compared the distribution of MICA alleles from the healthy controls in this study to those reported for Southern and Northern Han populations (22,23), as well as for Korean (24), Thai (25), American-Caucasian (23), and Afro-American populations (23). As shown in Table 4, no dramatic differences were observed in the MICA allelic distribution between the Han populations from different areas of China (P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The MICA polymorphism and its LD with HLA-B have been recently investigated for a southeastern Chinese Han population residing in Zhejiang Province [29], where MICA*045 was rarely found (1.5%) and significant LD of 6 A new MICA allele, MICA*059, was observed in this population. MICA*059 appeared to be carried on an HLA-B*1301 haplotype, suggesting that this new MICA allele is evolutionarily linked to and possibly derived from MICA*045 through a single mutation event.…”
Section: Discussionmentioning
confidence: 99%